Analisis Kesulitan Kemampuan Pemecahan Masalah Pada Pesera Didik Dalam Pembelajaran Fisika - Nurul, Dede (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
The purpose of this research is to find out the difficulties of learners in solving problems in physics learning. The research was conducted on students of class XI of SMAN 1 Ciawi Tasikmalaya Regency. The research subjects are students of class XI SMAN 1 Ciawi Tasikmalaya Regency with a total of 36 students. The research method used in research is qualitative descriptive research, with reference to problem-solving strategies. Analysis of learning outcomes is done by analyzing test results in quantitative descriptive. The learning outcomes measured in this study were only in the cognitive realm based on the scores obtained by students at each meeting. The results of the study that the difficulties faced by students in solving physics problems include: 1) Lack of ability to associate physical concepts in solving physics problems. 2) Less systematic and less attention to the steps of solving the problem, focused only on the final result. 3) A weak understanding of the principles and rules of physics